Rebranding Logo sebagai Upaya Peningkatan Value Added pada UMKM Menyenk Cafe - Hendry Hermawan; Ratih Mukti Azhar (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
This journal examines the benefits of logo rebranding as an effort to increase value added in MSMEs (Micro, Small and Medium Enterprises). In the case of this journal, it focuses on Menyenk Cafe MSMEs located in the Tenggilis Mejoyo Village area, namely MSMEs in the field of food and beverages whose sales have decreased and the lack of attractiveness of buyers. In this case we use a community service approach between us as researchers and the owner of Menyenk Cafe in Bina Desa activities with the theme of entrepreneurship and we go directly to MSMEs in the place where we conduct Bina Desa in Tenggilis Mejoyo Village. In rebranding the logo is adjusted to the identity and needs to increase value added to Menyenk Cafe MSMEs that experience sales and attractiveness constraints. So that this logo rebranding effort is expected to be successful in increasing sales and attracting buyers.